The Micro-Hospital: 5G Telemedicine-Based Care - Stefano, George B; Kream, Richard M (Medical science monitor basic research, 2018)
Today's medical service delivery platforms provide everything from small urgent care 'offices' to large medical centers. Since 2007, an intermediate entity for care has been established, namely, the micro-hospital. Micro-hospitals are 24-hour, small inpatient facilities with an average of 2 to 10 beds, designed to provide a diversity of healthcare services consistent with community demands. In addition, they seek to combine a cost-effective healthcare vehicle with potential time-dependent triage/transfer capabilities to a nearby large medical center. This smaller cost-effective entity represents an ideal vehicle for telemedicine, whereby specialists are always on hand for interpretation and consultation, with minimal patient waiting. In all likelihood, telemedicine, including cloud data storage and retrieval, will develop at a faster pace due to emerging 5G technology. Appropriate modification of the micro-hospital may also lead to creation of specialized centers devoted to endocrine and metabolic disorders, pulmonary diseases, and addiction medicine, which are certainly within the realm of medical necessity.
Keywords: lékařská informatika; využití lékařské informatiky; Humans; Hospitals; Medical Informatics; lidé; nemocnice; Telemedicine; telemedicína; Medical Informatics Applications